Tokovi okroglega lesa v Sloveniji - Ščap, Špela (Gozdarski vestnik, 2021)
Roundwood flow analyses are an essential tool for showing the state of the forest-timber sector in a country or region. The volume and structure of roundwood coming annually from forests and its further use indicate the sector's state and the possibilities for its further development. Roundwood flows can also serve as a basis for designing various scenarios for developing the forest-timber industry and for formulating appropriate policies. The article's main purpose is to present the structure of roundwood production and its use in the last ten years. Particular emphasis is put on the presentation of foreign trade with roudwood, since the trends in foreign trade change markedly. Considering production, the roundwood represents a high share of wood export, thus placing Slovenia on the tail of European countries. Current trends point to increased domestic roundwood processing and the revival of the domestic wood processing industry, even though the COVID-19 epidemic and emergencies in the year 2020 affected the domestic and foreign markets.
Keywords: analiza tokov; okrogli les; poraba; zunanja trgovina